Visual Strategies as Infographic Modeling Course Material for Deaf Students at Universitas Sahid Surakarta (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Since 2014 Universitas Sahid Surakarta has accepted deaf students. However, starting in 2018, communication problems emerged in the delivery of material from lecturers to deaf students. This is because: 1. 90% of deaf students in Visual Communication Design cannot read written sentences that are too long and 2. Deaf students' digital applications to translate the voice of the lecturer when explaining do not function properly. This study aims to produce icon designs for lecture material infographics for deaf students of Visual Communication Design Study Program, Universitas Sahid Surakarta and test the feasibility of the design. Therefore, the research method is carried out using qualitative methods. By using data triangulation in conducting data validation. This is done based on the problems that arise, so it is necessary to find a cause-and-effect relationship by looking at the symptoms, conditions, and phenomena that occur. The results achieved are visual strategies in the form of icons from representative words/sentences arranged to form infographics from information about lecture material. This is done because the way of understanding communication, one way of learning language for the deaf is by maximizing the sense of sight as a tool in receiving information stimuli through visual language. One of them is using visual language in the form of infographics that are formed through visual strategies according to the information needs of deaf students in the Visual Communication Design study program.